Trend analysis and regional tumor incidence in Germany for testicular cancer between 2003 and 2014. (16th July 2019) - Brandt, M. P.; Gust, K. M.; Bon, D.; Tsaur, I.; Thomas, C.; Neisius, A.; Haferkamp, A.; Herrmann, E.; Bartsch, G.
Abstract: Background: Testicular germ cell tumor (TGCT) is one the most common solid tumors in men between the age of 15 and 35 with an overall incidence rate of 1–1.5 %. Epidemiologic studies have demonstrated different incidence patterns in western civilized countries with overall rising incidence trends. Objective: To analyze differences in regional tumor incidence rates for TGCT and perform a trend analysis for TGCT between 2003 and 2014 in Germany. Material and methods: TGCT cases in Germany which were diagnosed between 2003 and 2014 were provided by the Robert‐Koch‐Institute, Berlin. For statistical analysis, cluster and spatial scan tests according to Kulldorff were used for cases with seminoma and non‐seminoma. Results are presented in administrative districts and graphically illustrated. We performed a trend‐analysis in order to evaluate age‐adjusted incidence trends in Germany. Tests were two‐sided with a level of significance of α=0.05. Results: In total we included 35, 066 patients. Overall, 22, 634 cases had newly diagnosed seminoma and 12, 432 were diagnosed as non‐seminoma. Maximum incidence of seminoma and non‐seminoma was observed for age‐group 38–40 years and 26–28 years, respectively. No second peak for the incidences of seminoma and non‐seminoma with respect to age were observed. Cluster analysis revealed areas with high and low incidence rates as well as slightly different spatial distribution in Germany between seminoma and nonseminoma. Furthermore, there was no significant increase in age‐adjusted incidence rates over the reviewed time period in both cohorts. Discussion: In this study differences in reginal tumor incidence rates for seminoma and non‐seminoma are reported with both tumor entities revealing distinct clusters. Furthermore, tumor incidence trends for seminoma and nonseminoma between 2003 and 2014 were stable which might indicate the beginning of a plateau phase for TGCT incidence rates in Germany. Conclusion: In this analysis we were able to identify regions with significantly higher tumor incidence rates for both seminoma and non‐seminoma which were specific for these two subtypes. Furthermore, trend analysis revealed a steady incidence rate for testicular cancer in Germany.